Advancing Eucalyptus Genomics: Cytogenomics Reveals Conservation of Eucalyptus Genomes - Ribeiro, Teresa; Barrela, Ricardo M.; Bergès, Hélène; Marques, Cristina; Loureiro, João; Morais-Cecílio, Leonor; Paiva, Jorge A. P. (Frontiers in Plant Science, 2016)
The genus Eucalyptus encloses several species with high ecological and economic value, being the subgenus Symphyomyrtus one of the most important. Species such as E. grandis and E. globulus are well characterized at the molecular level but knowledge regarding genome and chromosome organization is very scarce. Here we characterized and compared the karyotypes of three economically important species, E. grandis, E. globulus and E. calmadulensis, and three with ecological relevance, E. pulverulenta, E. cornuta and E. occidentalis, through an integrative approach including genome size estimation, fluorochrome banding, rDNA FISH and BAC landing comprising genes involved in lignin biosynthesis. All karyotypes show a high degree of conservation with pericentromeric 35S and 5S rDNA loci in the first and third pairs, respectively. GC-rich heterochromatin was restricted to the 35S locus while the AT-rich het pattern was species-specific. The slight differences in karyotype formulas and distribution of AT-rich het, along with genome sizes estimations, supports the idea of Eucalyptus genome evolution by local expansions of heterochromatin clusters. The unusual co-localization of both rDNA with AT-rich het was attributed mainly to the presence of silent transposable elements in those loci. The cinnamoyl CoA reductase gene (CCR1) previously assessed to linkage group 10 (LG10) was clearly localized distally at the long arm of chromosome 9 establishing an unexpected correlation between the cytogenetic chromosome 9 and the LG10. Our work is novel and contributes to the understanding of Eucalyptus genome organization which is essential to develop successful advanced breeding strategies for this genus.